Three molecular pathways model colorectal carcinogenesis in Lynch syndrome. Issue 1 (23rd February 2018) - Ahadova, Aysel; Gallon, Richard; Gebert, Johannes; Ballhausen, Alexej; Endris, Volker; Kirchner, Martina; Stenzinger, Albrecht; Burn, John; von Knebel Doeberitz, Magnus; Bläker, Hendrik; Kloor, Matthias
Abstract : Lynch syndrome is caused by germline mutations of DNA mismatch repair (MMR) genes. MMR deficiency has long been regarded as a secondary event in the pathogenesis of Lynch syndrome colorectal cancers. Recently, this concept has been challenged by the discovery of MMR‐deficient crypt foci in the normal mucosa. We aimed to reconstruct colorectal carcinogenesis in Lynch syndrome by collecting molecular and histology evidence from Lynch syndrome adenomas and carcinomas. We determined the frequency of MMR deficiency in adenomas from Lynch syndrome mutation carriers by immunohistochemistry and by systematic literature analysis. To trace back the pathways of pathogenesis, histological growth patterns and mutational signatures were analyzed in Lynch syndrome colorectal cancers. Literature and immunohistochemistry analysis demonstrated MMR deficiency in 491 (76.7%) out of 640 adenomas (95% CI: 73.3% to 79.8%) from Lynch syndrome mutation carriers. Histologically normal MMR‐deficient crypts were found directly adjacent to dysplastic adenoma tissue, proving their role as tumor precursors in Lynch syndrome. Accordingly, mutation signature analysis in Lynch colorectal cancers revealed that KRAS and APC mutations commonly occur after the onset of MMR deficiency. Tumors lacking evidence of polypous growth frequently presented with CTNNB1 and TP53 mutations. Our findings demonstrate that Lynch syndrome colorectal cancers can develop through three pathways, with MMR deficiency commonly representing an early and possibly initiating event. This underlines that targeting MMR‐deficient cells by chemoprevention or vaccines against MMR deficiency‐induced frameshift peptide neoantigens holds promise for tumor prevention in Lynch syndrome. Abstract : What's new? Whether mutations in mismatch repair (MMR) genes play an initiating or a secondary role in colorectal carcinogenesis in Lynch syndrome is unclear. To better understand the pathogenic process, the authors of this study developed a Lynch syndrome model delineating three molecular pathways of colorectal cancer formation. Some colorectal cancers were found to grow from MMR‐proficient adenomas after secondary inactivation of the MMR system. However, most colorectal cancers developed from MMR‐deficient precursor lesions, either via an adenomatous phase or as nonpolypous lesions. The findings underline the importance of prevention measures targeting MMR‐deficient cells in the clinical management of Lynch syndrome.